2022
DOI: 10.1101/2022.02.07.479466
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The direction and timing of theta and alpha traveling waves modulate human memory processing

Abstract: To support a range of behaviors, the brain must flexibly coordinate neural activity across widespread brain regions. One potential mechanism for this coordination is a traveling wave, in which a neural oscillation propagates across the brain while organizing the order and timing of activity across regions (Ermentrout & Kleinfeld, 2001; Muller et al., 2018). Although traveling waves are present across the brain in various species (Lubenov & Siapas, 2009; Zhang et al., 2018; Davis et al., 2020), their po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 101 publications
(144 reference statements)
9
27
0
Order By: Relevance
“…Furthermore, the timing (or phase) of traveling waves also plays a critical role in human cognition. In our recent study, we have shown that the timing of a wave precisely defines fast and slow response times, in a working memory task (51). These results may be similar to a set of findings in animals, where the phase of traveling beta oscillations predicted stimulus detection in visual perception (17).…”
Section: Features Of Traveling Wavessupporting
confidence: 83%
See 4 more Smart Citations
“…Furthermore, the timing (or phase) of traveling waves also plays a critical role in human cognition. In our recent study, we have shown that the timing of a wave precisely defines fast and slow response times, in a working memory task (51). These results may be similar to a set of findings in animals, where the phase of traveling beta oscillations predicted stimulus detection in visual perception (17).…”
Section: Features Of Traveling Wavessupporting
confidence: 83%
“…Given that we found evidence for the existence of traveling waves across several frequency bands such as the delta, theta, alpha, and beta ranges (14,15,43,51), it raises an important question of how the waves in these bands relate to each other. Previous studies have shown that theta and beta traveling waves in the human insula travel independently of each other during resting-state (43).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations